Bacterial Toxin Effector-Membrane Targeting: Outside in, then Back Again - Geissler, Brett (Frontiers in Cellular and Infection Microbiology, 2012)
Pathogenic bacteria utilize multiple approaches to establish infection and mediate their toxicity to eukaryotic cells. Dedicated protein machines deposit toxic effectors directly inside the host, whereas secreted toxins must enter cells independently of other bacterial components. Regardless of how they reach the cytosol, these bacterial proteins must accurately identify their intracellular target before they can manipulate the host cell to benefit their associated bacteria. Within eukaryotic cells, post-translational modifications and individual targeting motifs spatially regulate endogenous host proteins. This review focuses on the strategies employed by bacterial effectors to associate with a frequently targeted location within eukaryotic cells, the plasma membrane.